Absolute distance measurement in a combined-dispersive interferometer using a femtosecond pulse laser. (24th November 2015) - Wu, Hanzhong; Zhang, Fumin; Meng, Fei; Liu, Tingyang; Li, Jianshuang; Pan, Liang; Qu, Xinghua
Abstract: In this paper, a ranging system using dispersive interferometry is developed with a femtosecond pulse laser, aiming to eliminate the measurement dead zones by using a greatly unbalanced Mach–Zehnder interferometer. The distance can be measured by the frequency of the spectral modulation. We indicate that the integer number of the pulse-to-pulse length can be determined by changing the repetition frequency. In the short distance measurement, the results show an agreement within 1.5 μ m compared with an incremental He-Ne laser in the 1 m measurement range. We do large-scale experiments on a long optical rail using a typical Michelson interferometer, and an agreement well within 25 μ m is obtained in a range up to 75 m, corresponding to a relative precision of 3.3 × 10 −7 . Additionally, we experimentally optimize the system set-up to minimize the measurement uncertainty.